The first five years of teaching in a small town in Ceará - Fernandes, Francisca Risolene (2021)
A differentiated training for each teacher, the insertion process of fellow teachers who have recently arrived in public schools for a period of less than five years, and especially how the core management receives these professionals with insertion policies generates a lot of uneasiness among education professionals. Based on this theme, the following problematic was elaborated to guide the study: in which we discuss how the managing nucleus deals with the insertion of new teachers in elementary school? In order to answer the central research question, a scientific essay was conducted with the purpose of discussing and forwarding reflections about the insertion and/or induction strategies and, at the same time, discuss the induction process of three public school teachers. A qualitative approach and a study classified as a case study were used, and it was developed between April and May 2021, through a whatsapp questionnaire with open questions.